Diseño y control de una cabina automatizada para la captura de imágenes de miembro inferior residual transtibial - López Pérez, Manuel Alejandro; Alemón, Beatriz; Ballesteros, Mariana; Fuentes, Rita; Huegel, Joel (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
This paper presents the design of an automated cabin for thermal image capture. The device aims to improve precision during the capture and processing of the image in an isolated space. The thermographic pictures are used in the analysis of the residual human limb for transtibial amputee subjects. This study could serve as a non-invasive method seeking a correlation between the quality of the socket and the thermal activity on the amputee stump. The proposed cabin provides a standard process to acquire thermal images of the regions of interest from the participant stump reducing human errors, the variance between samples, and provides an isolated workspace to reduce environmental noise. The methodology includes the computed assisted design of all mechanical elements, the electronic instrumentation for the automation, the interface, and the control algorithm to regulate the thermal camera movements, and numerical simulations to depict the functionality.